Indian patient use of cancer euphemisms: Association with psychological outcomes and health behaviours. Issue 7 (19th May 2020) - Epton, Tracy; Chittem, Mahati; Tanikella, Ravali; Rajappa, Senthil; Sinha, Sudha; Harris, Peter R
Abstract: Objective: Euphemisms may be used to reduce the threat associated with the word "cancer." Cancer may be particularly threatening in Indian culture due to the myths surrounding its cause and prognosis. This study explored the prevalence of euphemism use by Indian patients and the relationship among euphemism use and illness cognitions, affect, health behaviour, and spontaneous self‐affirmation (a behaviour associated with dealing with threat). Methods: In total, 350 cancer patients in India were recruited to take part in a study exploring patients' experiences of, and thoughts about, having an illness. They responded to a questionnaire measuring illness perceptions, coping strategies, anxiety, depression, health behaviours, and spontaneous self‐affirmation. Patients were asked what words they used to describe their illness; euphemism users were those who used a euphemism (ie, non‐medical term) as a first word. Results: About 51% of patients used a euphemism as a first word. Those with less education, unskilled employment, a lower income, and more children were more likely to be euphemism users. Euphemism users reported (a) weaker illness perceptions (less personal control, greater reporting of symptoms, and less understanding of their condition), (b) less use of 3 of 14 coping strategies, (c) less likelihood of spontaneously self‐affirming, and (d) fewer healthy eating days. Conclusions: Euphemism use in patients was not related to distress but was related to negative illness perceptions and use of fewer coping strategies, suggesting that we need further study about the extent to which euphemisms signal issues in psychological adaptation to cancer diagnosis.